Foliar Application of Boron Nanoencapsulated in Almond Trees Allows B Movement Within Tree and Implements Water Uptake and Transport Involving Aquaporins - Rios, Juan J.; Lopez-Zaplana, Alvaro; Bárzana, Gloria; Martinez-Alonso, Alberto; Carvajal, Micaela (Frontiers in Plant Science, 2021)
Nanotechnologies bring to agriculture new forms of nutrient fertilization applications, which could be used to reduce contamination and increase efficiency. In this work, foliar fertilization with nanoencapsulated boron (B) was studied in comparison to free B application in young B-deficient almond trees grown under controlled environment. The study of the B movement within the plant in relation with the leaf gas exchange, water relations parameters, and root hydraulic conductance was carried out. Also, the expression of aquaporins (PIP and TIP) was studied in accordance to water uptake and transport parameters to establish the effectiveness of the different B treatments. The results obtained were associated to a high concentration of B obtained with nanoencapsulated B, provided by the higher permeability of the carrier nanovesicles, which allowed B to reach the cell wall more efficiently. The increase in water uptake and transport obtained in these plants is discussed as being related to structural and regulatory roles in the cell wall/plasma membrane relationship that could regulate the aquaporin expression improving water relations. Also, the increase in PIPs (mainly PIP2.2) expression to the nanoencapsulated B applied could be related to the need for B and water transport, and the fine regulation of TIP1.1 in relation to the B concentration in tissues provide an important feature in the re-mobilization of B within the cell.